Geological settings and seismic attributes in albian carbonates reservoirs – Southwest of Campos Basin (RJ – Brazil) - Do Nascimento, Luana Fernandes [UNESP]; Vincentelli, Maria Gabriela Castillo [UNESP]; De Jesus Perinotto, Joée Alexandre [UNESP] (My University, 2017)
The importance of carbonates reservoirs in the global oil stage justifies studies aimed to determine the distribution of their physical properties. Moreover, as these reservoirs are considered complex in a geophysical context, it is necessary to reduce the geological uncertainty related to the main reservoir facies distribution. Based on this previous issue, this work outlines a method of obtaining pseudo-physical properties such as porosity (φ) and density (ρ) of two carbonate reservoirs using quantitative analysis of seismic attribute maps. These intervals were delimited by a structural-stratigraphic trap (faults and lateral variation of carbonate facies) at the Albian level from the Southwest of Campos Basin, where an oil producer field is located in a structural high. The reservoirs are of good quality, with an average porosity of 20%, directly calculated from well logs (mainly NPhi). This property features a high variation throughout the field, justified by the heterogeneity of the carbonate rock. Qualitatively, the reservoir distribution was obtained from the integration of structural, isoproperties and seismic attribute maps, which were applied above each reservoir surface maps; among them, the Maximum Negative Amplitude, Maximum Absolute Amplitude and Minimum Amplitude showed a linear relation at the correlation crossplot of density and porosity (R2>0.74). So, such process showed to be successful in characterization of the mentioned properties.
Keywords: Carbonates physical properties; Porosity; Seismic interpretation; Well correlation